Interaction of Stoned and Synaptotagmin in synaptic vesicle endocytosis. - Fergestad, T.; Broadie, K. (Journal of Neuroscience, 2001)
The Drosophila dicistronic stoned locus encodes two distinctive presynaptic proteins, Stoned A (STNA) and Stoned B (STNB); STNA is a novel protein without homology to known synaptic proteins, and STNB contains a domain with homology to the endocytotic protein AP50. Both Stoned proteins colocalize precisely with endocytotic proteins including the AP2 complex and Dynamin in the "lattice network" characteristic of endocytotic domains in Drosophila presynaptic terminals. FM1-43 dye uptake studies in stoned mutants demonstrate a striking decrease in the size of the endo-exo-cycling synaptic vesicle pool and loss of spatial regulation of the vesicular recycling intermediates. Mutant synapses display a significant delay in vesicular membrane retrieval after depolarization and neurotransmitter release. These studies suggest that the Stoned proteins play a role in mediating synaptic vesicle endocytosis. We have documented previously a highly specific synaptic mislocalization and degradation of Synaptotagmin I in stoned mutants. Here we show that transgenic overexpression of Synaptotagmin I rescues stoned embryonic lethality and restores endocytotic recycling to normal levels. Furthermore, overexpression of Synaptotagmin I in otherwise wild-type animals results in increased synaptic dye uptake, indicating that Synaptotagmin I directly regulates the endo-exo-cycling synaptic vesicle pool size. In parallel with recent biochemical studies, this genetic analysis strongly suggests that Stoned proteins regulate the AP2-Synaptotagmin I interaction during synaptic vesicle endocytosis. We conclude that Stoned proteins control synaptic transmission strength by mediating the retrieval of Synaptotagmin I from the plasma membrane.